“Angiokinase” - Molecular Weights of Proteins Representing a Perivascular Plasminogen Activator - Auerswald, W; Binder, B; Doleschel, W (Thrombosis and Haemostasis, 1971)
By means of gel filtration (Sephadex G-150) of precipitates originating from human cadaver vessel perfusates the molecular weights of a perivascular plasminogen activator “angiokinase” were determined. Maximum angiokinase activity was found at the molecular weight 61,000, high activities at 30,500 and 120,000, and traces of activity at 15,000, 45,700, and 76,000. Presumably angiokinase is the product of polymerization of a basic unit (mol. weight 30,500) or its subunit (mol. weight 15,000).